Science communication in times of crisis - Hohaus, Pascal (Discourse approaches to politics, society, and culture, 2022)
"This volume addresses demands on external and internal science communication in times of crisis. The contributions discuss present crises such as COVID-19 (e.g. vaccination campaigns or political reactions towards the pandemic in the context of science scepticism), and climate change (e.g. plausibility judgements or the role of scientists). They also relate their approaches to past crises, e.g. 9/11 or the Galileo affair. This volume is unique in that it is interdisciplinary from a theoretical and methodological perspective. In that respect, the authors apply concepts from corpus linguistics, discourse analysis, rhetoric, news values analysis, pragmatics and terminology research to various types of data, such as newspaper headlines, Tweets, open letters, corpora or glossaries. The case studies are situated within different cultural contexts, with various languages being examined, i.e. Polish, Arabic, English, French, German, and Spanish. Elevating our understanding of the interface of science communication and crisis communication, this collection of articles proves valuable to scholars and students from linguistics, communication science, political science, sociology and philosophy of science"--